Mexico and the principal Asian economies. Some indexes - Covián G., Miguel Ángel (Revista Mexicana de Política Exterior, 2022)
This paper presents and comments on some statistical tables that illustrate the similarities and differences between Mexico and some of the most dynamic Asian economies (Japan, Hong Kong, Singapore, Korea, Thailand, Malaysia and Indonesia). Comparative tables are produced based on information from the 1998 Report on Human Development, of the United Nations Development Program, related to territorial area, population, economic production, per capita product, population employed in the different economic sectors, productivity, and saving and investment, among other indexes of these eight countries.